Gypsum-Dependent Effect of NaCl on Strength Enhancement of CaO-Activated Slag Binders - Sungwon Sim; Hwan Lee; Dongho Jeon; Haemin Song; Woo Sung Yum; Dohoon Kim; Jung-Il Suh; Jae Eun Oh (Applied Sciences, 2018)
This study explores the combined effect of NaCl and gypsum on the strength of the CaO-activated ground-granulated blast furnace slag (GGBFS) binder system. In the CaO-activated GGBFS system, the incorporation of NaCl without gypsum did not improve the strength of the system. However, with the presence of gypsum, the use of NaCl yielded significantly greater strength than the use of either gypsum or NaCl alone. The presence of NaCl largely increases the solubility of gypsum in a solution, leading to a higher concentration of sulfate ions, which is essential for generating more and faster formations of ettringite in a fresh mixture of paste. The significant strength enhancement of gypsum was likely due to the accelerated and increased formation of ettringite, accompanied by more efficient filling of pores in the system.